2010
DOI: 10.1259/dmfr/76385066
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of cone beam computed tomography in temporomandibular joints with soft tissue pathology

Abstract: Objective: The aim of the study was to evaluate the usefulness of cone beam CT (CBCT) in temporomandibular joints (TMJs) with soft tissue pathology. Methods: 106 TMJs of 55 patients with temporomandibular disorder (TMD) were examined by MRI and CBCT. MR images were used for the evaluation of disc displacement, disc deformity, joint effusion and obscurity of temporal posterior attachment (TPA). CBCT images were evaluated for the presence or absence of osseous abnormalities. The x 2 test was used to analyse the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 31 publications
6
34
0
3
Order By: Relevance
“…Diagnosis of the degenerative changes affecting the TMJ can be done more accurately using CBCT which provides images at a lower exposure than CT 2 The results of our study revealed that in coronal section, convex morphology was more commonly observed(49%) followed by round(23%).This was in accordance with the study conducted by Yale et.al(1966) 5 . However, in a study conducted by Subhashini et.al.…”
Section: Discussion:-supporting
confidence: 91%
See 1 more Smart Citation
“…Diagnosis of the degenerative changes affecting the TMJ can be done more accurately using CBCT which provides images at a lower exposure than CT 2 The results of our study revealed that in coronal section, convex morphology was more commonly observed(49%) followed by round(23%).This was in accordance with the study conducted by Yale et.al(1966) 5 . However, in a study conducted by Subhashini et.al.…”
Section: Discussion:-supporting
confidence: 91%
“…Anatomical knowledge of the temporomandibular joint is one of the foundations for the clinical practice that allows the understanding of pathological alterations, diagnostic evaluation and appropriate choice of therapeutic paths 1 .The temporomandibular joint is a unique joint that can be affected by different kinds of hard and soft tissue abnormalities 2 The bony components of TMJ need a careful study since the changes in these components may imply functional disorders and pain 1 . Temporomandibular joint disorders are a subdivision of musculoskeletal pathologies which act as a source of orofacial pain of non dental origin 3 .These temporomandibular joint disorders are frequently associated with certain degenerative bony changes that include; Flattening, Erosion, Osteophytes etc, all of which involve the bony components of TMJ.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
“…33 This was substantiated in a clinical study comparing CBCT and MRI. 34 From these comparison studies and the accuracy studies in the previous section, it is clear that CBCT and CT are highly comparable regarding evaluation of the cortical bone. Thus, CBCT or CT is the method of choice, depending on the availability, for the assessment of cortical bone details of the TMJ because of the multiplanar reformation capabilities and high spatial resolution.…”
mentioning
confidence: 69%
“…The erosion process represents the initial stage of a bone degenerative process, it is possible to observe the density reduction area and the adjacent cortical bone, which leads deformity in the size or shape of the condyle 8,12,15 . It is not uncommon for the patient has multiple changes to the same condyle (flattening , erosion , osteophytes and subchondral cysts) (Figure 4) .…”
Section: Clinical Casesmentioning
confidence: 99%